2005
DOI: 10.1590/s0101-20612005000200020
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy-entropy compensation based on isotherms of mango

Abstract: 13635-900, Pirassununga, SP. A quem a correspondência deve ser enviada. ENTHALPY-ENTROPY COMPENSATION BASED ON ISOTHERMS OF MANGO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
4
13
0
8
Order By: Relevance
“…The behavior of inversion of the temperature effect on the isotherm of adsorption observed in the present study ( Figure 2) is in agreement with Telis-Romero et al (2005). These authors claim that some studies reported such inversion of the temperature effect for water activity higher than 0.70 in products with high sugar contents, such as fruits, which can be explained by an increase in the solubility of sugar in the water.…”
Section: Resultssupporting
confidence: 92%
“…The behavior of inversion of the temperature effect on the isotherm of adsorption observed in the present study ( Figure 2) is in agreement with Telis-Romero et al (2005). These authors claim that some studies reported such inversion of the temperature effect for water activity higher than 0.70 in products with high sugar contents, such as fruits, which can be explained by an increase in the solubility of sugar in the water.…”
Section: Resultssupporting
confidence: 92%
“…This result is in accordance with those obtained by Gabas et al (2007) and Martinelli, Gabas and Telis-Romero (2007). Some studies have reported this inversion in the temperature effect at water activities above 0.7 for products with high sugar content such as fruits (TELIS-ROMERO et al, 2005;TSAMI et al, 1990), which can be explained by an increase in sugar solubility in water caused by increasing temperature.…”
Section: Resultssupporting
confidence: 92%
“…Algunos estudios han reportado este cruzamiento en función de la temperatura en actividades de agua por encima de 0.7 para productos con altos contenidos de azúcar, como es el caso de frutas (TELIS-ROMERO et al, 2005;TSAMI et al, 1990), los cuales son explicados por un aumento en la solubilidad de azúcares en agua causados por el aumento de temperatura.…”
Section: Materials Y Métodosunclassified